Pengaruh Motivasi dan Kemajuan Teknologi Terhadap Minat Investasi Saham - Bayu Tri Cahya; Nila Ayu Kusuma W. (Institut Agama Islam Negeri Padngsidimpuan, 2019)
Abstract“Yuk Nabung Saham”is a concept of a strong capital market industry campaign and national scale. This campaign aims to increase public awareness about the capital market in Indonesia, especially generation Y to invest in the capital market by buying shares regularly and periodically. This study aims to determine the effect of motivation and the influence of technological advancements on investment interest in generation Y in Kudus city. The research design is quantitative. The population and sample in this study are generation Y who knows about investments and who have invested in the stock market through the Indonesia Stock Exchange Investment Gallery Muria Kudus University. Data collection in this study using the questionnaire method and data analysis using multiple linear regression. The results of this study indicate that investment motivation and technological progress influence investment interest in the